Maternal to fetal transfer of vitamin C and vitamin E: effect on birth outcome in a Nigerian population - Ikaraoha, Ikechukwu Chidiebere; Mbadiwe, Nkeiruka Chigaekwu; Anetor, John Ibhagbemien; Nwadike, Constance Nnedimma; Oforofuo, Isreal Ojareva (Asian Journal of Medical Sciences, 2016)
Background: New evidence suggests that excessive production of reactive oxygen species give rise to oxidative stress which could impair fetal growth. Antioxidant vitamin C and vitamin E have vital role in physiological process of pregnancy and health of the developing fetus. Aims and Objectives: To determine the concentrations of vitamin C and vitamin E in pair-matched maternal and cord serum of newborns and to determine the relationship between maternal/cord serum vitamin C and vitamin E at delivery and birth outcomes. Materials and Methods: A total of 209 maternal and cord blood samples were collected during delivery for serum vitamin C and E determination. Birth outcomes; birth weight, birth length, head circumference, and Apgar score were determined. Result: Newborns had significantly higher levels of vitamin C as compared to their mothers, but had non-significant lower level of vitamin E. Levels of vitamin C and E in both maternal and cord serum were positively correlated to birth weight, birth length, head circumference and Apgar score. Conclusion: Maternal vitamin C and E had significant effects on birth outcomes. A positive correlation of vitamin C and E indicates that their status in mother does influence newborns status. Asian Journal of Medical Sciences Vol.7(4) 2016 49-54